Metal Artifact Reduction Sequence MRI Abnormalities in Asymptomatic Patients with a Ceramic-on-Polyethylene Total Hip Replacement. (5th April 2017) - Jennings, Jason M.; Martin, J. Ryan; Kim, Raymond H.; Yang, Charlie C.; Miner, Todd M.; Dennis, Douglas A.
Abstract : Background: Magnetic resonance imaging (MRI) is a commonly utilized screening modality in patients with a metal-on-metal (MoM) total hip replacement. The prevalence of clinically important fluid collections may be overestimated since these collections have been reported to occur in asymptomatic patients with MoM and other bearing surfaces. The purpose of this study was to determine the frequency and types of MRI-documented adverse local tissue reactions in asymptomatic patients with a ceramic-on-polyethylene (CoP) total hip replacement. Methods: Forty-four patients (50 hips) with a minimum 2-year follow-up after total hip arthroplasty with CoP implants and a Harris hip score of >90 were enrolled in this study. The inclusion criteria were the absence of hip pain and the availability of appropriate follow-up radiographs. All patients underwent a metal artifact reduction sequence (MARS) MRI scan to determine the presence of fluid collections in asymptomatic patients with a CoP bearing surface. Results: Fluid collections were observed in 9 (18%) of 50 asymptomatic hips in this cohort. There were 5 hips with intracapsular synovitis, and 2 of these hips had a thickened synovium. Extra-articular fluid collections with direct intracapsular communication were identified in 4 additional hips. Two of these hips had a thickened synovium. No signs of osteolysis or evidence of adverse local tissue reactions were noted on radiographs at the most recent follow-up. Conclusions: This study revealed that fluid collections are not uncommon after total hip arthroplasty with CoP implants. Synovial thickening may be present and is more prevalent than has been reported in previous studies involving metal-on-polyethylene (MoP) bearing surfaces. The clinical importance and natural history of these findings remain unknown. Level of Evidence: DiagnosticLevel IV . See Instructions for Authors for a complete description of levels of evidence.